2022
DOI: 10.1111/ppc.13095
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of nurses' mindfulness with their perception of individualized care: A cross‐sectional study

Abstract: Purpose: The objective of this study is to investigate the correlation of nurses' mindfulness with their perception of individualized care.Design and Methods: It was designed as a descriptive correlational study. Two hundred seventy-one nurses were included in this study. Findings:The mean total score was 4.20 ± 0.04 on the "Mindful Attention Awareness Scale" and 3.97 ± 0.04 on the "Individualized Care Scale-Nurse." There was a significant positive correlation between the mean total score on the scales and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Considering similar studies, it was revealed that gender variable significantly affected the perceptions of individualized care of nursing students (35)(36)(37). However, in some studies, it was observed that the gender factor did not affect the individualized care perceptions of nursing students and nurses (8,26,38). This may be due to the fact that the studies were conducted in different sample groups and on participants with different demographic structures.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Considering similar studies, it was revealed that gender variable significantly affected the perceptions of individualized care of nursing students (35)(36)(37). However, in some studies, it was observed that the gender factor did not affect the individualized care perceptions of nursing students and nurses (8,26,38). This may be due to the fact that the studies were conducted in different sample groups and on participants with different demographic structures.…”
Section: Discussionmentioning
confidence: 98%
“…It ensures that a unique care plan is developed based on the individual in question, their experiences, behaviors, thoughts and perceptions and that this plan is followed in practice. In this way, the nurse creates a keen understanding of the condition of the patient and rapidly notices any problems (7,8). When the literature was examined, it was observed that there were a limited number of studies examining the status of nursing students regarding individualized care (26,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations